Use of the Profunda Femoris Artery Perforator Flap for Reconstruction after Sarcoma Resection. Issue 12 (December 2020) - Karakawa, Ryo; Yoshimatsu, Hidehiko; Maeda, Erisa; Shibata, Tomoyoshi; Tanakura, Kenta; Kuramoto, Yukiko; Miyashita, Hiroki; Yano, Tomoyuki
Abstract : Background: Soft tissue sarcomas are rare neoplasms that can occur on any part of the body. The operative position for the resection is determined depending on the site of the soft tissue sarcomas; intraoperative repositioning may be needed for reconstruction. We present the profunda femoris artery perforator (PAP) flap harvest technique (wherein the flap can be used in any position), and suggest that the PAP flap transfer can eliminate the need for intraoperative repositioning. Methods: From December 2018 to January 2020, 7 patients with an average age of 68 years underwent reconstructions using a PAP flap after wide resection of STS. The mean defect size was 11.3 × 16.5 cm (range, 5.5–25 × 11–26 cm). The location of the defects was the medial thigh in 2 patients, the posterior thigh in 1, the popliteal fossa in 1, the groin in 1, and the buttock in 2. The PAP flap was elevated in the supine "frog-leg" position, the prone position, the jack-knife position, or the lateral "crisscross" position; the lateral decubitus position with the donor lower extremity on the bottom. Results: Of the 7 cases, the operations were performed in the supine "frog-leg" position in 3 cases, the prone position in 2 cases, the jack-knife position in 1 case, and the lateral "crisscross" position in 1 case. There were no intraoperative position changes in all cases. The mean size of the PAP flap was 8.7 × 19.9 cm (range, 6–11 × 17–24 cm). One patient had donor site dehiscence, which was treated conservatively. The PAP flaps survived completely in all cases. The mean follow-up period was 10.5 months (range, 6–17 months). Conclusion: Since the PAP flap elevation is feasible in every position, the PAP flap can be considered a versatile reconstruction option after sarcoma resection.